The effect of health consciousness on older adults’ health information-sharing intention: the mediating role of self-efficacy and social norms - An, Jing; Xiang, Ziyue; Wan, Kexin; Zhu, Xuanyu; An, Jinlong; Yang, Yujie (Frontiers in Public Health, 2025)
BackgroundIn the modern society where social media and aging are intertwined, how to promote older adults to integrate into the digital society and enjoy digital interests, to improve their quality of life and happiness, and promote active healthy aging has become an important topic today.MethodsBased on social cognition theory, we constructed a research model including health consciousness, self-efficacy, social norms, and health information-sharing intention (ISI) of older adults. A total of 225 valid questionnaires were collected through a questionnaire survey, and empirical analysis including reliability test, exploratory factor analysis, confirmatory factor analysis, hypothesis test, and mediation effect test was conducted.ResultsThe results show that older adults’ health consciousness, self-efficacy, and social norms have a significant positive effect on health information sharing. Health consciousness has a positive effect on social norms and older adults’ self-efficacy. Furthermore, social norms and older adults’ self-efficacy mediate the relationship between health consciousness and health information-sharing intention, respectively.ConclusionThis study considers health consciousness as a key research variable, which not only further explores the internal drivers of sharing health information among older adults but also provides a new perspective and strategies for promoting healthy aging.